Symposium 8: How is it for You? The Impact of Networked Learning on Educational Institutions: Symposium Introduction - Higgison, Carol (Proceedings of the International Conference on Networked Learning, 2004)
Educational institutions, both further and higher education, are becoming places of almost endless change, and the growth of networked learning is only one of the many changes our institutions are adapting to, or embracing. The changes include rapid growth in both student numbers and student diversity, decreased government funding per student, institutions becoming involved in new markets and new business ventures to increase income, and the growth of borderless education (www.obhe.ac.uk). Educational Institutions are expected to embrace the rapidly changing technologies that are potentially allowing for different modes of teaching. The UK government recently published a new document – Towards a Unified E-learning Strategy (www.dfes.gsi.gov.uk/consultations2/16/) and Charles Clarke, secretary of state for education and skills exhorts HEIs to engage in the challenge of making full use of new technologies (THES, 11th July 2003). The government’s paper recognises that web-based instruction has already been developed in higher education and that it is seen as increasingly important by these institutions (Traxler, 2002). Most HE and FE institutions are now engaging with the networked learning in some form or another.